Determination of the Long‐Term Properties in Laminate‐Thickness Direction of Textile‐Reinforced Thermoplastic Composites under Compression Using Time–Temperature Superposition1 . Issue 3 (22nd December 2015) - Pohl, Martin; Kupfer, Robert; Koch, Ilja; Modler, Niels; Hufenbach, Werner A.
Abstract : The application of Time–Temperature Superposition (TTS) for the determination of isochronous stress–strain diagrams of textile‐reinforced thermoplastic composites under compressive load in laminate thickness direction is evaluated. Creep experiments are carried out at various temperature and load levels. The creep curves are assembled to master curves using horizontal and vertical shifting. These curves are compared to long‐term creep data and an isochronous stress–strain diagram is determined. Abstract : Time–temperature superposition is evaluated experimentally for textile‐reinforced thermoplastic composites under compressive load in laminate thickness direction. Creep curves at various temperature and load levels are assembled to master curves using horizontal and vertical shifting. The master curves are compared to long‐term creep data and an isochronous stress–strain diagram is determined.